ASUMSI DALAM ILMU - Wendi Rais (JEM Jurnal Ekonomi dan Manajemen, 2020)
Science requires an assumption, an assumption is needed to overcome the study so that a problem does not become wide, and it is this assumption that provides direction and the basis for our study activities. Science has three assumptions about empirical objects. First, assuming certain objects have similarities to one another. Second, the assumption that an object does not change in a certain period of time, and the third is Determinism, which is a scientific assumption which assumes that a symptom is not an accidental event. Every symptom has a certain pattern that is fixed with the same sequence of events.